2003
DOI: 10.1063/1.1629783
|View full text |Cite
|
Sign up to set email alerts
|

Intersublevel photoresponse of (In,Ga)As/GaAs quantum-dot photodetectors: Polarization and temperature dependence

Abstract: We report on the polarization dependence of intraband photoresponse of (In,Ga)As/GaAs quantum-dot device structures for light polarized parallel and perpendicular to the layers. Strong photoresponse due to intersublevel transitions induced by both s- and p-polarized infrared light was observed. Within the plane of the layers, it is found that the photoresponse for s-polarized light aligned along the [110] crystallographic direction is virtually identical to that in the [1̄10] direction, suggesting that, at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The main benefit in using the QD approach stems from 3D quantum confinement, which (1) enables normal incidence absorption by modifying the optical transition selection rule, and, (2) increases the photo-excited carrier lifetime by reducing optical phonon scattering via the ''phonon bottleneck'' mechanism [1][2][3][4][5][6]. However, QDs also have some drawbacks that need to be addressed.…”
Section: The Dot-in-the-well Infrared Photodetectormentioning
confidence: 98%
“…The main benefit in using the QD approach stems from 3D quantum confinement, which (1) enables normal incidence absorption by modifying the optical transition selection rule, and, (2) increases the photo-excited carrier lifetime by reducing optical phonon scattering via the ''phonon bottleneck'' mechanism [1][2][3][4][5][6]. However, QDs also have some drawbacks that need to be addressed.…”
Section: The Dot-in-the-well Infrared Photodetectormentioning
confidence: 98%
“…QDIPs ranging from single element detectors (Su et al, , 2006Ariyawansa et al, 2005aAriyawansa et al, , 2008Aslan et al, 2003;Kochman et al, 2003;Liu et al, 2001;Jiang et al, 2003;Raghavan et al, 2002;Krishna et al, 2003;Bhattacharya et al, 2005;Jiang and Singh, 1997;Chakrabarti et al, 2005) to FPAs Krishna et al, 2007;Gunapala et al, 2007a;Tsao et al, 2007) have been reported. In addition to the aforementioned advantages, QDIPs are reported to have improved radiation hardness (Ryzhii and Khmyrova, 2002;Ryzhii, 1996;Leon et al, 2000) and polarization-sensitive spectral responses (Aslan et al, 2003;Pal et al, 2003). QDIPs operating at temperatures above 77 K (Kochman et al, 2003;Sergeev et al, 2002;Ye and Campbell 2002;Phillips et al, 1998;Maimon et al, 1998;Pan et al, 1998;Lim et al, 2007) indicate the possibility of developing uncooled or thermoelectrically (TE) cooled IR imaging systems.…”
Section: Terahertz Qd Detectorsmentioning
confidence: 99%
“…The main benefit in using the QD approach stems from 3D quantum confinement, which (1) enables normal incidence absorption by modifying the optical transition selection rule, and, (2) increases the photo-excited carrier lifetime by reducing optical phonon scattering via the "phonon bottleneck" mechanism [1][2][3][4][5][6]. However, QDs also have some drawbacks that need to be addressed.…”
Section: Introductionmentioning
confidence: 98%
“…QDs are nanometer-scale islands that form spontaneously on a semiconductor substrate due to lattice mismatch. QD infrared photodetectors (QDIPs) with properly engineered dots have been predicted theoretically to have significant advantages over quantum well infrared detectors (QWIPs) [1][2][3][4][5][6][7][8]. QDIPs are fabricated using robust wide band gap III-V materials which are well suited to the production of highly uniform LWIR arrays.…”
Section: Introductionmentioning
confidence: 99%